Effectiveness of Xylitol Chewing Gum in patients with Orthodontic Pain - Ayesha Shafiq, Amra Minhas Abid, Asad Ur Rehman, Maria Khan, Shezonia Tariq, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Pain during active orthodontic treatment is a common experience. Orthodontic treatment involves active and passive stretching and compression of periodontal ligaments as well as of adjacent soft tissues which is the basic cause of pain. Pain is one of the important factors which have impact on oral health-related quality of life (OHRQOL) because it hinders the proper plaque control by the patient. Aim: To ascertain the efficacy of xylitol chewing gums on the reduction in pain levels during the first week of orthodontic treatment. Methods: This is a case control study in which 60 orthodontic patients were selected and randomly allocated into two groups. 30 patients were in control group and 30 were treated with Xylitol gum. Patients were advised to take xylitol chewing gum 3-5 times per day and not to take any analgesics. 2 weeks follow up is advised with filled Visual Analog Scale form. Results: The average age of patients was 19.93±3.04 years. There were 39(65%) male and 21(35%) female. At 24 hours and at 7 days, the mean pain score was significantly low in Xylitol gum groups as compare to control groups. Conclusion: In present study, Xylitol gum had higher analgesic efficacy than control group. So Xylitol gums can be good replacement for orthodontic pain relief that has an advantage of minimum side effects in contrast to ibuprofen.